PROBLEMS OF RURAL SCHOOL EDUCATION SYSTEM IN INDIA. - Dr. Paras Jain & Rachna Billaiya (International Journal of Research Science and Management, 2018)
Our government has made so many policies and amendments for uplifting the education standard. Our government is spending on education be to ensure that all children have access to government schools and to raise the quality of education in those schools. One of the major problems is quality of education due to education system itself and students. Present study is focused finding of teachers views regarding problems of rural issues.